Titik temu: Central Market / Muhammad Syafiq Hazwan Mohamad Jaafar ... [et al.] - Mohamad Jaafar, Muhammad Syafiq Hazwan; Abd Rahman, Nur Adilla; Ahmad Noorhani, Nur Maizura; Mustapha, Arniatul Aiza (College of Built Environment, 2023)
The outbreak of Covid-19 has been affected internationally. This situation has had a significant impact on the tourism industry, with severe consequences for jobs an businesses.